Investigating Anecdotal Text Writing Ability In Tenth Grade Learners - Sepianti, Emlis; Sulastri, Sulastri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the ability of class X students at MAN 01 Kota Bengkulu in writing anecdotal texts, particularly focusing on the structure and linguistic features of the text. Methodology: This study used a descriptive method with a quantitative approach. The population included all 317 tenth-grade students of MAN 01 Kota Bengkulu in the 2022/2023 academic year. The sample of 23 students was selected using purposive sampling. Data were collected through a writing test with a rubric assessing five structural components of anecdotal texts and linguistic features. The average score formula was used for data analysis. Main Findings: The findings show that students’ ability to write anecdotal texts is generally categorized as good with an average score of 76.71. Specifically, the abstraction aspect was excellent (12.3), orientation good (14.9), crisis good (14.4), reaction excellent (12.4), coda excellent (11.4), and linguistic elements excellent (11.4). These results indicate that most students have mastered the structure and language use of anecdotal texts effectively. Novelty/Originality of this study: This study provides a focused evaluation of students’ writing based on the complete five-part structure of anecdotal texts combined with linguistic criteria. Unlike prior studies, this research offers a comprehensive assessment using a targeted rubric and highlights specific strengths and weaknesses across each structural and linguistic component, contributing to curriculum-based evaluation methods in writing instruction.